Composite report on projects funded through the Australian Universities Teaching Committee 2000-2003. - Hicks, Owen (Australian Universities Teaching Committee, 2004)
This composite report on ten projects funded by the Australian Universities Teaching Committee between 2000 and 2003 draws together feedback and analysis of discipline-based projects addressing learning outcomes and curriculum development in Arts, Biotechnology, Business, Information and Communication Technologies, Law and Nursing, as well as issue-based projects on Assessment, ICT in Flexible Learning, Teaching Large Classes and Sessional Teaching. Analysis of the reports and resources produced by the projects and feedback from project teams, steering groups and potential 'consumers' (front-line academics and educational developers) formed the basis of this report. [p.iii]